2014
DOI: 10.1371/journal.pone.0103141
|View full text |Cite
|
Sign up to set email alerts
|

NOA1, a Novel ClpXP Substrate, Takes an Unexpected Nuclear Detour Prior to Mitochondrial Import

Abstract: The mitochondrial matrix GTPase NOA1 is a nuclear encoded protein, essential for mitochondrial protein synthesis, oxidative phosphorylation and ATP production. Here, we demonstrate that newly translated NOA1 protein is imported into the nucleus, where it localizes to the nucleolus and interacts with UBF1 before nuclear export and import into mitochondria. Mutation of the nuclear localization signal (NLS) prevented both nuclear and mitochondrial import while deletion of the N-terminal mitochondrial targeting se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 38 publications
(51 reference statements)
3
29
0
Order By: Relevance
“…We demonstrated that simultaneous overexpression of ClpX and NOA1 led to the complete degradation of NOA1 without modulating ClpP protein levels [29]. This supported the idea that ClpX was the limiting factor in determining ClpXP efficiency in muscle cells [29].…”
Section: Clpx Is Selectively Up Regulated During Myogenesis Recensupporting
confidence: 73%
See 4 more Smart Citations
“…We demonstrated that simultaneous overexpression of ClpX and NOA1 led to the complete degradation of NOA1 without modulating ClpP protein levels [29]. This supported the idea that ClpX was the limiting factor in determining ClpXP efficiency in muscle cells [29].…”
Section: Clpx Is Selectively Up Regulated During Myogenesis Recensupporting
confidence: 73%
“…Furthermore, we confirm the involvement of a retrograde transcriptional regulation pathway mediated by the UPR mt transcription factor CHOP. In conclusion, we show that the main features of the C. elegans [9][10][11][12][13]29,33] UPR mt are conserved in mammalian cells and present ClpX overexpression as model for the mammalian UPR mt . To knockdown ClpP in cell culture, we cloned the following shRNA target sequences into the U6+2tetO [34] plasmid: ClpP sh1 5 '-GAA GCA CCT TCC ATT ACT TCT-3' and ClpP sh2 5'-GCC TCC TTC ACC TTG ACA AAC-3'.…”
Section: Accepted Manuscriptmentioning
confidence: 65%
See 3 more Smart Citations